2014
DOI: 10.1177/1748006x14558899
|View full text |Cite
|
Sign up to set email alerts
|

Study of on-line condition monitoring and fault feature extraction for marine diesel engines based on tribological information

Abstract: Reliability and safety issues on marine diesel engines have been received and still need considerable attentions. The literature review indicates that a large amount of failures are caused by abnormal wear of the diesel engine components. It is therefore essential to monitor the engine condition using the tribological information. To further promote the oil monitoring technology into industrial application, a new on-line condition monitoring and remote fault diagnosis system for marine diesel engines is propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The online ferrographic sensor samples the wear debris image from the oil, and IPCA is calculated with the image digital processing technology [10]. Among the oil parameters collected by this system, Yan and Li in [11] find that IPCA and oil viscosity are the two parameters reflecting the oil condition best.…”
Section: A Remote Fault Diagnosis Technologymentioning
confidence: 99%
“…The online ferrographic sensor samples the wear debris image from the oil, and IPCA is calculated with the image digital processing technology [10]. Among the oil parameters collected by this system, Yan and Li in [11] find that IPCA and oil viscosity are the two parameters reflecting the oil condition best.…”
Section: A Remote Fault Diagnosis Technologymentioning
confidence: 99%
“…Experimental results showed that the fusion technology has a higher reliability and applicability compared to the single detection technology. Ebersbach et al [140] combined vibration with oil analysis and wear debris analysis to establish an expert system to realize the condition monitoring of rotating machinery. Tests results showed that the expert system has a higher reliability and universality compared to manual experience to judge the operation status of the machine.…”
Section: Multi-sensors Fusion Technologymentioning
confidence: 99%
“…To improve system reliability and prolong remaining useful life (RUL), predictive maintenance (PdM) or condition-based maintenance (CBM) strategies rely on efficient condition monitoring (CM). Among numerous online and offline CM technologies [1][2][3][4], lubricant condition monitoring (LCM) provides early-stage warning ability and multiple other indicators to define the system state [5][6][7]. Wear debris concentration (WDC) is considered as an indicator that can closely define both the lubricant and system state.…”
Section: Introductionmentioning
confidence: 99%
“…Several other model-based approaches [13][14][15], statistical approaches [16][17][18][19] and hybrid approaches [20], [21] have been widely adopted for degradation trend analysis. These approaches pose certain limitations: (1) For model-based approaches, accurate mathematical modeling of the complex system with non-linearity and uncertainty is difficult; (2) Statistical approaches are single feature focused and not able to pick patterns and auto-state observations, and tend to be harder for modeling of non-monotonic degradation trends; (3) For hybrid methods, modeling of the complex system considering the environmental and external factors still remains a challenge.…”
Section: Introductionmentioning
confidence: 99%